การเมืองของประชาธิปไตยแบบปรึกษาหารือในกระบวนการพัฒนา : ศึกษากรณีการจัดการน้ำในจังหวัดระยอง - สุรางค์รัตน์ จำเนียรพล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purpose of this research is to answer how deliberative democracy links to Thai democratic politics under the conditions of unequal interest and power in political development. There are three issues to be studied. The first is the development of deliberative democracy concept in Thailand. The second is the politics of interest and power in deliberative democracy process. The third is the limitations and conditions of deliberative democracy promotion in Thailand. The research is done in the case of water management in Rayong Province by clearly focusing on the conflict of power and interest. The study finds that there are pushes on institutional deliberative democracy from the health assembly and the council of the community. They establish deliberative democratic institution in form of health assembly and council. However, both institutions do not work under the condition of power and interest of the water management in Rayong Province. At the same time, the process of deliberative democracy can partly resolve the conflict of interest and power in water management because there are limits of interest and power networks, limits of bureaucratic politics of water management, appropriateness between deliberative democracy and the other kinds of participation. The conditions of deliberative democracy promotion consist of the acceptance of deliberative democracy from government sectors, the decentralized structure of decision making process, and the acceptance of various stakeholders’ participation. The balanced power among stakeholders ensures the rational process of making and changing their preferences.